The sensitivity of cartilage contact pressures in the knee joint to the size and shape of an anatomically shaped meniscal implant. Issue 8 (1st June 2015) - Khoshgoftar, M.; Vrancken, A.C.T.; van Tienen, T.G.; Buma, P.; Janssen, D.; Verdonschot, N.
Abstract: Since meniscal geometry affects the cartilage contact pressures, it is essential to carefully define the geometry of the synthetic meniscal implant that we developed. Recently, six independent modes of size- and shape-related geometry variation were identified through 3D statistical shape modeling (SSM) of the medial meniscus. However, this model did not provide information on the functional importance of these geometry characteristics. Therefore, in this study finite element simulations were performed to determine the influence of anatomically-based meniscal implant size and shape variations on knee cartilage contact pressures. Finite element simulations of the knee joint were performed for a total medial meniscectomy, an allograft, the average implant geometry, six implant sizes and ten shape variations. The geometries of the allograft and all implant variations were based on the meniscus SSM. Cartilage contact pressures and implant tensile strains were evaluated in full extension under 1200 N of axial compression. The average implant induced cartilage peak pressures intermediate between the allograft and meniscectomy and also reduced the cartilage area subjected to pressures >5 MPa compared to the meniscectomy. The smaller implant sizes resulted in lower cartilage peak pressures and compressive strains than the allograft, yet high implant tensile strains were observed. Shape modes 2, 3 and 6 affected the cartilage contact stresses but to a lesser extent than the size variations. Shape modes 4 and 5 did not result in changes of the cartilage stress levels. The present study indicates that cartilage contact mechanics are more sensitive to implant size than to implant shape. Down-sizing the implant resulted in more favorable contact mechanics, but caused excessive material strains. Further evaluations are necessary to balance cartilage contact pressures and material strains to ensure cartilage protection and longevity of the implant.